Ethical Climate and Organizational Dissent: Insights from White-Collar Employees - Çiğdem Kaya (Business Ethics and Leadership)
Organizational dissent refers to employees’ expression of disagreement or opposing views on organizational policies and practices. Such dissent typically arises from employees’ contradictory opinions regarding company policies, procedures, and practices. An organization’s ethical climate reflecting employees' shared perceptions regarding company policies, practices, and procedures can significantly influence how and when dissent is expressed. This study investigates the impact of ethical climate on organizational dissent by analyzing data from 356 white-collar employees across various industries in Istanbul, Turkey. Data were collected using convenience sampling and analyzed using SPSS statistics software program. Reliability, factor, correlation and regression analysis were performed on the obtained data, and hypothesis was tested. The findings reveal that specific dimensions of ethical climate distinctly shape dissent behaviors. The 'laws and professional codes' dimension, which emphasizes adherence to formal standards, is positively associated with constructive articulated dissent, where employees directly and openly express concerns. In contrast, the “personal morality” dimension negatively contributes to questioning articulated dissent, suggesting that high individual ethical standards may discourage critical questioning of organizational practices. Additionally, an ethical climate marked by “friendship” negatively contributes to displaced dissent, where employees are less likely to voice complaints to external parties or indirect channels. These insights offer valuable implications for managers seeking to create an ethical climate that fosters constructive dissent while minimizing potentially harmful forms of discontent, promoting a culture of openness and trust.